A consistent multi‐scale derivation of a micro‐plane model within the framework of RVE homogenisation. Issue 1 (17th December 2018) - Storm, Johannes; Kaliske, Michael
Abstract: The micro‐plane model is an approach to describe complex anisotropic material behaviour by a set of uniaxial deformation states. The model is widely applied in the context of concrete materials and has various formulations for anisotropic damage, creep and plastic material behaviour. The paper contributes to this class of material models by a consequent multi‐scale derivation of a micro‐plane‐like model within the framework of RVE homogenisation. The new approach preserves the elegant and efficient model structure and yields a thermodynamically consistent scale transition. The model derivation allows to clearly state the conditions on the micro‐structure and thereby to classify the micro‐plane models and the known extensions with respect to their micro‐structural motivations.